Unusual (1)H NMR chemical shifts support (His) C(ɛ)(1)—H⋅⋅⋅O⩵C H-bond: Proposal for reaction-driven ring flip mechanism in serine protease catalysis - Ash, Elissa L. (The National Academy of Sciences, 2000)
(13)C-selective NMR, combined with inhibitor perturbation experiments, shows that the C(ɛ)(1)—H proton of the catalytic histidine in resting α-lytic protease and subtilisin BPN′ resonates, when protonated, at 9.22 ppm and 9.18 ppm, respectively, which is outside the normal range for such protons and ≈0.6 to 0.8 ppm further downfield than previously reported. They also show that the previous α-lytic protease assignments [Markley, J. L., Neves, D. E., Westler, W. M., Ibanez, I. B., Porubcan, M. A. & Baillargeon, M. W. (1980) Front. Protein Chem. 10, 31–61] were to signals from inactive or denatured protein. Simulations of linewidth vs. pH demonstrate that the true signal is more difficult to detect than corresponding signals from inactive derivatives, owing to higher imidazole pK(a) values and larger chemical shift differences between protonated and neutral forms. A compilation and analysis of available NMR data indicates that the true C(ɛ)(1)—H signals from other serine proteases are similarly displaced downfield, with past assignments to more upfield signals probably in error. The downfield displacement of these proton resonances is shown to be consistent with an H-bond involving the histidine C(ɛ)(1)—H as donor, confirming the original hypothesis of Derewenda et al. [Derewenda, Z. S., Derewenda, U. & Kobos, P. M. (1994) J. Mol. Biol. 241, 83–93], which was based on an analysis of literature x-ray crystal structures of serine hydrolases. The invariability of this H-bond among enzymes containing Asp-His-Ser triads indicates functional importance. Here, we propose that it enables a reaction-driven imidazole ring flip mechanism, overcoming a major dilemma inherent in all previous mechanisms, namely how these enzymes catalyze both the formation and productive breakdown of tetrahedral intermediates.